2022
DOI: 10.1200/jco.22.00912
|View full text |Cite|
|
Sign up to set email alerts
|

Phase II Randomized Study of Ramucirumab and Pembrolizumab Versus Standard of Care in Advanced Non–Small-Cell Lung Cancer Previously Treated With Immunotherapy—Lung-MAP S1800A

Abstract: PURPOSE Resistance to immune checkpoint inhibition (ICI) in advanced non–small-cell lung cancer (NSCLC) represents a major unmet need. Combining ICI with vascular endothelial growth factor (VEGF)/VEGF receptor inhibition has yielded promising results in multiple tumor types. METHODS In this randomized phase II Lung-MAP nonmatch substudy (S1800A), patients ineligible for a biomarker-matched substudy with NSCLC previously treated with ICI and platinum-based chemotherapy and progressive disease at least 84 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 27 publications
2
67
0
1
Order By: Relevance
“…Interestingly, early results from studies investigating the combination of pembrolizumab and lenvatinib, a multi-tyrosine kinase inhibitor, have shown improved efficacy and response durability in several advanced solid tumors, including preliminary data for patients with treatment-refractory NSCLC [69]. More recently, promising results were also presented for the combination of pembrolizumab and ramucirumab, a VEGFR-2 antibody, in pre-treated patients with NSCLC, although the subgroup of patients with BMs was not explicitly evaluated [70]. Outcomes of patients with NSCLC and BMs treated with combination therapies are reported in Table 2.…”
Section: Icis and Target Agentsmentioning
confidence: 99%
“…Interestingly, early results from studies investigating the combination of pembrolizumab and lenvatinib, a multi-tyrosine kinase inhibitor, have shown improved efficacy and response durability in several advanced solid tumors, including preliminary data for patients with treatment-refractory NSCLC [69]. More recently, promising results were also presented for the combination of pembrolizumab and ramucirumab, a VEGFR-2 antibody, in pre-treated patients with NSCLC, although the subgroup of patients with BMs was not explicitly evaluated [70]. Outcomes of patients with NSCLC and BMs treated with combination therapies are reported in Table 2.…”
Section: Icis and Target Agentsmentioning
confidence: 99%
“…Bevacizumab + atezolizumab is a standard first-line treatment for patients with advanced hepatocellular carcinoma (5). Reckamp et al (26) performed a phase II study to evaluate the efficacy of ramucirumab + pembrolizumab compared with investigator's choice of care in patients with advanced NSCLC who previously received chemotherapy + PD-1 blockade. Even following resistance to prior ICI, ramucirumab with pembrolizumab improved OS compared with standard care, with ORR of 22% (26).…”
Section: Univariate Analysismentioning
confidence: 99%
“…82 However, the recent Lung-MAP S1800A substudy indicated that the combination of ramucirumab plus pembrolizumab might be a promising approach following immunochemotherapy in patients with NSCLC, including SCC. 83 A total of 136 patients were randomized to receive ramucirumab plus pembrolizumab or investigator's choice of standard care (docetaxel ± ramucirumab, gemcitabine or pemetrexed). In the overall dataset, the combination significantly improved OS versus standard of care (median 14.5 vs. 11.6 months; HR 0.69 [80% CI, 0.51-0.92]).…”
Section: Other Current and Emerging Treatment Optionsmentioning
confidence: 99%